2007
DOI: 10.1002/dvdy.21166
|View full text |Cite
|
Sign up to set email alerts
|

The DVE changes distal epiblast fate from definitive endoderm to neurectoderm by antagonizing nodal signaling

Abstract: To assess the function of the distal visceral endoderm (DVE) of embryonic day 5.5 (E5.5) embryos, we established a system to directly ablate the DVE and observe the consequences after culture. When the DVE was successfully ablated, such embryos (DVE-ablated embryos) showed deregulated expression of Nodal and Wnt3 and ectopically formed the primitive streak at the proximal portion of the embryo. The DVE and anterior visceral endoderm (AVE) are implicated in the development of neurectoderm. We found that the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Microsurgical ablation of the AVE at the onset of gastrulation leads to forebrain truncations [10] and ablation at 5.5dpc abolishes the expression of anterior neuroectoderm markers [11]. Analysis of mouse mutants where gene function has been specifically lost in extra-embryonic tissues has further demonstrated the role of the AVE in forebrain specification [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Microsurgical ablation of the AVE at the onset of gastrulation leads to forebrain truncations [10] and ablation at 5.5dpc abolishes the expression of anterior neuroectoderm markers [11]. Analysis of mouse mutants where gene function has been specifically lost in extra-embryonic tissues has further demonstrated the role of the AVE in forebrain specification [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…The leading role of the primary AVE was suggested through microsurgical ablation of the primary AVE, which resulted in a wider defect in remaining VE migration (Miura and Mishina 2007). Importantly, inducible genetic lineage ablation of Lefty1 -expressing cells clearly showed that the secondary AVE does not migrate anteriorly if early Lefty1 -expressing primitive endoderm is eliminated (Takaoka et al 2011).…”
Section: Anteroposterior Axis Patterningmentioning
confidence: 99%
“…AVE ablation experiments and disruption of gene function specifically in the VE lead to forebrain truncations, indicating that the function of the AVE is essential for head development (Arkell and Tam, 2012;Miura and Mishina, 2007;Rhinn et al, 1998;Shawlot et al, 1999;Stern and Downs, 2012;Stuckey et al, 2011b;Thomas and Beddington, 1996;Varlet et al, 1997). AVE ablation experiments and disruption of gene function specifically in the VE lead to forebrain truncations, indicating that the function of the AVE is essential for head development (Arkell and Tam, 2012;Miura and Mishina, 2007;Rhinn et al, 1998;Shawlot et al, 1999;Stern and Downs, 2012;Stuckey et al, 2011b;Thomas and Beddington, 1996;Varlet et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, explant recombination experiments and tissue grafts failed to uncover any anterior neural inducing activity of AVE cells. This could contribute to protecting these precursors from the influence of primitive streak derived signals (Miura and Mishina, 2007). Is there an additional role for DVE and AVE cells in controlling head development?…”
Section: Introductionmentioning
confidence: 99%